Christianity and Law in the Enlightenment - John Witte Jr (Australian Journal of Law & Religion)
The European and American Enlightenment movements of 1688 to 1815 transformed the Western legal tradition, notably in areas of constitutional law, criminal law, private law, legal and political theory, and legal education. Particularly the American and French Revolutions effected massive and sometimes violent changes to traditional patterns of law, politics, and society — separating church and state and placing a new premium on democratic rule of law by the general will and public opinion. These legal reforms were grounded in part in new Enlightenment liberal beliefs in deism, rationalism, individualism, and nationalism — ideas that came to strong expression in the many new constitutions and codes issued in the later 18th and 19th centuries. Even so, Enlightenment legal reformers often worked side by side with Christian legal reformers, and they reconstructed traditional Christian legal teachings more than they created laws anew. As a consequence, until the mid-19th century, there was more continuity than discontinuity between Enlightenment-based legal teachings and practices and those of the Western Christian tradition. The Enlightenment, however, provided new secular logics for many of the traditional laws that it adopted and then adapted, and these secular teachings would later fuel the more strident post-Christian, if not anti-Christian, legal campaign of modern liberalism.